The liver X receptor pathway is highly upregulated in rheumatoid arthritis synovial macrophages and potentiates TLR-driven cytokine release. Issue 12 (23rd February 2013) - Asquith, Darren Lee; Ballantine, Lucy E; Nijjar, Jagtar Singh; Makdasy, Manhal Khuder; Patel, Sabina; Wright, Pamela B; Reilly, James H; Kerr, Shauna; Kurowska-Stolarska, Mariola; Gracie, J Alastair; McInnes, Iain B
Abstract : Objectives: Macrophages are central to the inflammatory processes driving rheumatoid arthritis (RA) synovitis. The molecular pathways that are induced in synovial macrophages and thereby promote RA disease pathology remain poorly understood. Methods: We used microarray to characterise the transcriptome of synovial fluid (SF) macrophages compared with matched peripheral blood monocytes from patients with RA (n=8). Results: Using in silico pathway mapping, we found that pathways downstream of the cholesterol activated liver X receptors (LXRs) and those associated with Toll-like receptor (TLR) signalling were upregulated in SF macrophages. Macrophage differentiation and tumour necrosis factor α promoted the expression of LXRα. Furthermore, in functional studies we demonstrated that activation of LXRs significantly augmented TLR-driven cytokine and chemokine secretion. Conclusions: The LXR pathway is the most upregulated pathway in RA synovial macrophages and activation of LXRs by ligands present within SF augments TLR-driven cytokine secretion. Since the natural agonists of LXRs arise from cholesterol metabolism, this provides a novel mechanism that can promote RA synovitis.